Investigating modal integration of public transport and non-motorised transport in the City of Johannesburg: A case of the Roodepoort CBD - Prince, Matshika Lindokuhle (University of the Witwatersrand, Johannesburg, 2024)
This study explored the integration of non-motorized transport (NMT) with public transport in the City of Johannesburg, particularly the Roodepoort CBD. The research investigates the status of NMT infrastructure and public transport services in the city, identifying gaps and opportunities for integration. A comprehensive literature review was conducted to understand the factors influencing successful integration and to highlight best practices from other cities worldwide. The study examined the causes of transport fragmentation and emphasizes the importance of addressing these challenges to achieve seamless integration and analyses key enabling factors for successful integration, such as infrastructure planning and design, intermodal facilities, collaboration and coordination, policy, and regular support. Case studies of successful integration of public transport systems Globally are presented to gain practical insights for the implementation of integration strategies. Primary data was collected through interviews with key stakeholders and commuters and field observations were conducted to assess the existing NMT infrastructure and its integration with public transport. Convenience and purposive sampling methods were employed to select participants for the interviews and the data collected is analysed through thematic analysis, allowing for the identification of key themes and pattens relevant to the integration of NMT and public transport in the Roodepoort CBD. The findings of this study reveal that there is a possibility and opportunity for modal integration to occur within the Roodepoort CBD. However, there are various factors that need to be addressed such as the safety and security of pedestrians and the enforcement of regulations in terms of non-motorised transport facilities being used for other means such as street vending. The study concludes by providing recommendations to support the facilitation of this integration of NMT and public transport in the Roodepoort CBD.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Modal Integration; Public transport; Non-Motorised transport; City of Johannesburg; Roodepoort CBD; SDG-11: Sustainable cities and communities